Islam - The future civilization of mankind: Challenges and responses - Shehu, Fatmir (Journal of Education and Social Science (JESOC), 2016)
Ongoing bloodsheds and conflicts witnessed by most of today's worlds population despite their racial, social, cultural, political, and religious differences, on the one hand, and the developments in sciences, industry, infrastructure, arts and especially in information technology, on the other, are believed to be the real challenges encountered by contemporary people and especially the Muslims. What are the causes of these challenges? Do they have intellectual, economic, political or social dimension? How to respond to them? Who is responsible for the cause of these challenges – man or God? Islam with its sources of knowledge – Qur’an and Sunnah, claims to provide for Muslims and humanity as a whole the proper measures to respond to contemporary challenges. Definitely, Islam offers to humanity an enduring and authentic civilization with a transcendental nature that promotes holistic justice, peaceful coexistence, mutual respect and better understanding. The thrust of this study is on four main contemporary challenges witnessed especially by Muslims, i.e., the intellectual, economic, political and social and how to respond to them. The main objectives of this study are to exhibit the role of Islamic civilization in responding to contemporary challenges and to show its unique paradigm shift in shaping the future civilization of mankind. The descriptive and analytical methods will be employed in the entire study. The author of this paper strongly believes that this study will contribute to the revival of Muslims’ understanding of Islamic civilization and its application to their day-to-day individual, familial, communal, and social aspects of life. Besides, it will add a new asset of knowledge to the existing knowledge and will be a reference for young students, intellectuals, scholars, leaders, governors, and researchers.